Penatalaksanaan Fisioterapi Pada Kasus Bronkiektasis Di Balai Besar Kesehatan Paru Masyarakat Surakarta - Hanendya, Kharisa Lintang, Totok Budi Santoso, SST. FT., MPH (2016)
Background: Bronchiectasis is a chronic disease characterized by progressive dilatation of the bronchi and bronchioles which are settled and followed by thickening of the bronchial wall. This situation caused by infection of viruses or chronical bacteria. Physiotherapy as health workers play a role in dealing with cases Bronchiectasis, with the aim to restore lung function and reduce the problems that exist. In this case the problem of physiotherapy include impraiment, functional limitation and disability. In the face of this physiotherapy using nebulizer, infrared ray and chest therapy. Purpose: The purposes of physiotherapy include shortterm that decreases breathless, sputum production and muscle spasm, and the long term includes that prevents complication and increase life quality and activity tolerance. Method: Method in this case, the modality that is used infrared, nebulizer and chest therapy. The measurement of breathlessby using borg scale, pain by using VDS, sputum checking by using stetoskop, Activity Daily Living by usinglondon chest activity daily living scale Result: After doing therapy for 6 time, it was obtained the result breath tight measurement T1: 4 to T6: 3, decreasing pain includes meliputi nyeri diam T1: 0 to T6: 0, nyeri tekan T1: 3 toT6: 2, nyeri gerak T1: 4 to T6: 2, sputum production from beginning therapy until the end of therapy is decreasing its productivity. The physical activity and the patient functional are more increasing. Conclusion: Nebulizer, infrared and chest therapy are able to decrease breath tight, pain, sputum production and to increase activity daily living.